A preliminary survey on the understanding and application of digital and emphatic engagement of the construction constituents in Surabaya. Issue 1 (November 2021) - Nugraha, P; Jonathan, M; Listio, A
Abstract: This survey was actually triggered by this seminar topic, and applied to construction constituents in Surabaya. The Digital aspects derived from literature reviews are: Building Information Modelling, Augmented Reality, Mobile Technology, Sensors, Drones, Photogrammetry, Artificial Intelligence, Robotics, 3D Printing & Big Data analysis. The Emphatic Engagement aspects are in Integrated Project Delivery system and in serving the client's needs. Survey questions were focused on the understanding on the digital aspects, and where they got the information from. Further questions on the application of both Digital and Empathic Engagement aspects. The best understanding on Digital Aspects are about Mobile Technology and Drones. Least understanding about augmented reality, robotics and smart sensors. Best application of Digital aspects is in CAD, which unfortunately is not fully a BIM technology. Least applications are on Robotics and 3D printing. Best application of Emphatic Engagement is "having same vision/mission", while the least applications are on "BIM faster work" and "BIM conflict resolving".